Brain glucose transporters: relationship to local energy demand - Duelli, Roman; Kuschinsky, Wolfgang (Physiology, 2001)
Glucose, the major fuel in the brain, is transported across the cell membranes by facilitated diffusion mediated by glucose transporter proteins. Essentially two types of glucose transporters are localized in the membranes of brain endothelial cells, astrocytes, and neurons. Their densities are well adjusted to changes in local energy demand.